Effect of the Bone Graft on the Surface Microhardness of Endodontic Biomaterials - Shahi, Shahriar; Rahimi, Saeed; Yavari, Hamid Reza; Ghasemi, Negin; Rezaie, Yashar; Mirzapour, Samira (Iranian Endodontic Journal, 2018)
Introduction: During periapical surgery, using of bone products in large endodontic lesions, is a treatment option that could affect the properties of the retro-filling endodontic material. The aim of present study was to evaluate the effect of Osteon II bone powder on the surface microhardness of calcium-enriched mixture (CEM) and mineral trioxide aggregate (MTA). Methods and Materials: Each material was mixed and carried into 40 sterile custom-made plastic cylinders. Half of the samples in each group were exposed to Osteon II. All cylinders were submerged in simulated tissue fluid and incubated at 37°C and 100% relative humidity for 7 days. Surface microhardness values of each study group was attained using Vickers microhardness test. The data were analyzed statistically using two-way ANOVA and independent t-test at a significance level of 0.05. Results: The highest and lowest microhardness values were recorded in the MTA/without Osteon and MTA/with Osteon groups, respectively. Irrespective of the presence or absence of bone powder, the overall microhardness of CEM cement and MTA was not significantly different. In the MTA group, the presence of the powder resulted in a significant decrease (P<0.05) of the microhardness; however, its effect on CEM cement was not significant (P>0.05). Conclusion: Under the limitations of the present in vitro study, the presence of Osteon bone powder had no negative effect on the microhardness of CEM cement, contrary to its effect on MTA. Keywords: Bone Graft; Calcium-enriched Mixture; Hardness; Mineral Trioxide Aggregate